Pengaruh Kualitas Sistem, Layanan, dan Informasi Terhadap Pengguna Google Classroom Model DeLone and McLean - Dedi Priansyah; Fariszal Nova Arviantino; Yusuf Arif Setiawan; Dwiza Riana (LPPM Universitas Mulia, 2022)
Social distancing implemented due to COVID-19 in many countries, as well as Indonesia has caused all community activities to be limited and replaced with online activities. This is also applied to the world of education which has switched to distance learning systems, such as Google Classroom. This study aims to analyze the satisfaction of Google Classroom users, which is an alternative substitute system for teaching and learning activities in universities during the COVID-19 pandemic using the DeLone and McLean information system model. Research shows that this model can be used to analyze Google Classroom satisfaction and there is an influence between the elements of success, from the quality of information is 0.851, and the P-values are 0.082, system quality has a positive effect of 0.758, , service quality has a positive effect of 0.849 and the P-values are less than 0.001 so it can be concluded that service quality, system quality, and information quality have a positive and significant effect on user satisfaction.